The Influence of Learning Media and Interest on Student Absorption in Senior High Schools - Saputra, Hendrawan Adi; Putra, Alhadi Yan; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the effect of learning media and interest in learning on student absorption in high schools in Tanjung Lubuk District. The sample size taken was 89 students in high school in Tanjung Lubuk District. The sampling technique was purposive sampling, where the respondents taken were some high school students in Tanjung Lubuk District. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 73 statement items. The analysis technique used is multiple linear regression analysis. The results showed that there was an influence of learning media and learning interest on student absorption Second, the influence of learning media on student absorption Third, there was an influence of learning interest on student absorption.